Wearable sensors-based assistive technologies for patient health monitoring - Almujally, Nouf Abdullah; Khan, Danyal; Al Mudawi, Naif; Alonazi, Mohammed; Alhasson, Haifa F.; Jalal, Ahmad; Liu, Hui (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction:With the advancement of handheld devices, patient health monitoring using wearable devices plays a vital role in overall health monitoring.Methods:In this article, we have integrated multi-model bio-signals to monitor patient health data during daily life activities continuously. Two well-known datasets from ScientISST MOVE and mHealth have been analyzed. The purpose of this study is to explore the possibilities of using advanced bio-signals for monitoring patient vital signs during daily life activities and predicting favorable and more accurate health-related solutions based on current body health-related real-time measurements.ResultsWith the help of machine learning algorithms, we have observed classification accuracy of up to 94.67% using the mHealth dataset and 95.12% on the ScientISST MOVE dataset. Other performance indicators, such as recall, precision, and F1 score, also performed well.Discussion:Overall, integrating a machine learning model with bio-signals provides an enhanced ability to interpret complex real-time patient health monitoring for personalized care and overall smart healthcare.